Diversity of Soil Surface Arthropods Species in Taman Hutan Raya Sultan Syarif Hasyim, Riau Province - Angraini, Riris; Yoza, Defri; Pebriandi, Pebriandi (Universitas Labuhanbatu, 2024)
Soil surface arthropods are an important part of an ecosystem in the soil which has a role as a bioindicator of ecosystem balance and acts as a decomposer which can decompose organic materials and enrich the organic material content in the soil. This research aims to determine the diversity of soil surface arthropods species in three vegetation types in Taman Hutan Raya Sultan Syarif Hasyim. Sampling was conducted in Taman Hutan Raya Sultan Syarif Hasyim Riau Province in August 2023. This research used a purposive sampling method with a sampling technique using pitfall traps placed in three vegetation types (natural forest, shrubs and oil palm plantation). The overall results include 9 orders, 15 families, 26 species and a total of 2,027 individuals per hectare. In natural forests, there were 7 orders, 12 families, 20 species and 853 individuals per hectare, with a diversity index (H') of 2.27 (medium). In shrubs, there were 6 orders, 8 families, 12 species and 715 individuals per hectare, with an (H') of 2.17 (medium). In oil palm plantations, there were 4 orders, 5 families, 9 species and 549 individuals per hectare, with an (H') of 2.03 (medium)